Output of Saudi electronic newspapers and its relationship with the public readability for these newspapers: field study - Baothman, Raneem Yahya; Salem, Duaa Fathi (Journal of Humanities & Social Sciences, 2019)
The study aimed to identify the output of Saudi electronic newspapers and its relationship with the public readability for these newspapers, and the study was based on the method of media survey on a sample of (200) individual residents of Jeddah governorate who follow saudi electronic newspapers, using the theory of uses and saturations.The results of the study indicated: that the sample of the study follows the Saudi electronic newspapers less than an hour by 69, followed by follow from one hour to two hours by 18.5, and by 12.5 who follow it more than two hours, and 65 of the sample of the study explained that they sometimes agree with the form of Saudi electronic newspapers, While 24.5 do not always agree, and by 8.5% rarely agree, and 5 disapprove, the line (Riy- bold, Riy- semibold) came the best fonts used when writing the color and titles for the click sample study, the colors of the images and drawings came in the introduction of the click of the study sample, followed by the colors of the study sample The study also found that there is a correlation between the follow- up of the researchers to the Saudi electronic newspapers and the readability of those newspapers, and that there are some differences between the motives of the researchers using these newspapers and the methods of directing those newspapers.The study recommended that the designers of Saudi electronic newspapers and their sponsors seek to develop their websites in accordance with the wishes of the followers, and achieves the factors of the ease of readability in order to follow the public.
Keywords: producing electronic newspapers; Saudi electronic newspapers; reading